Safety and efficacy of a nurse-led elective cardioversion with etomidate for atrial arrhythmia in a tertiary hospital - Wael Zaher; Luigi Pannone; Kathleen Thayse; Klaus-Richard Ebinger; Emmanuel Tran-Ngoc; Carlo de Asmundis; Gian-Battista Chierchia; Antonio Sorgente (Heliyon, 2023)
Management of cardiac arrhythmias often requires direct current cardioversion (DCC) to restore sinus rhythm. This intervention varies greatly between countries and hospitals, mostly regarding the organization of an elective DCC, and the choice of the sedation. The aim of this study is to assess the safety and efficacy of an elective DCC performed in a cardiology day hospital, led by trained nurses, and using intravenous Etomidate as sedation. We performed a retrospective cohort study at a single tertiary hospital in Belgium. Data were collected from January 2017 to October 2020. A total of 788 electrical cardioversions were performed on 574 patients from 2017 to 2020. Age was 70.9 ± 10 years. Restoration of sinus rhythm was obtained in 89.5% of the patients. One (0.1%) patient experienced ischemic stroke within 24 h, despite adequate anticoagulation. There were 4 (0.5%) cases of transient sinus arrest requiring atropine. Three patients (0.4%) experienced respiratory depression, requiring bag-mask ventilation but not oro-tracheal intubation. There were no cases of hypotension. No periprocedural death was reported. In conclusion, an elective electrical cardioversion performed and led by trained nurses, using Etomidate as sedation, appears to be both safe and effective.